Influência dos NEO na evolução dos detritos espaciais - Santos, Marília dos Anjos (2018)
Space debris and Objects Near the Earth are two current topics and of great relevance to the scienti c community. The rst one due to the high probability of collision with the space vehicles (spacecraft, satellites, probes, etc); the second by virtue of the possibility of collision with the planet Earth, with potential for global e ects. Collisions caused by debris at orbital velocity can be highly damaging to the operation of vehicles in operation, also endangering the lives of astronauts in extravehicular activities; in addition, these collisions cause a greater accumulation of trash in the space, since they imply in new debris. Together, in the space environment, these debris can still interact with other larger bodies approaching the Earth, such as the NEOs, and due to the gravitational disturbances they can produce, debris can be inserted into the orbits of space vehicles, which were considered safe during the planning of the space missions, also occupying positions that compromise the \space windows", regions appropriate for safe launches of the Earth. In this context, this work aimed to study the e ects of gravitational interactions between NEOs and space debris in the LEO, MEO and GEO operating regions. Using the REBOUND integration package, we simulate numerically the N-body problem associated with this gravitational interaction dynamics. Our results indicate that the NEO interactions with the debris can cause changes in the eccentricities of these bodies, causing their scattering in the orbital regions. If the eccentricity is high, depending on the growth rate, the larger semi-axis of the orbit of the detritus increases, migration of the detritus to other orbital regions occurs. The most intense perturbations provide hyperbolic orbits to the debris. In this way, we veri ed that the gravitational e ect of NEO modi es the spatial distribution of the spatial debris disc in relation to its initial con guration